Typification and synonymy in Polystichum (Dryopteridaceae) from Chile and Argentina - Morero, Rita Ema (2016)
Polystichum Roth is one of the largest and most taxonomically challenging fern genera. South American species have a rich and complex nomenclatural history; many of the early names are inadequately typified. Based on extensive examination of original type material, we designate eleven lectotypes (including Aspidiummohrioides, A. montevidense f. imbricata, A. montevidense f. squamulosa, A. plicatum, A. pycnolepis, Dicksonia andina, Polystichum elegans, P. mohrioides f. latifolia, P. multifidum var. autranii, P. platyphyllum var. kurtziana, and Polypodium polystichoides), and one neotype (P. brongniartianum) for Polystichum taxa. Furthermore, three new synonyms are proposed.